Visceral Adipose Tissue: A New Target Organ in Virus-Induced Type 1 Diabetes - Zipris, Danny (Frontiers in Immunology, 2021)
Type 1 diabetes (T1D) is a proinflammatory disorders that leads to the specific destruction of insulin producing -cells and hyperglycaemia. Much of the knowledge about type 1 diabetes (T1D) has focused on mechanisms of disease progression such as adaptive immune cells and the cytokines that control their function, whereas mechanisms linked with the initiation of the disease remain unknown. It has been hypothesized that in addition to genetics, environmental factors play a pivotal role in triggering -cell autoimmunity. The BioBreeding Diabetes Resistant (BBDR) and LEW1.WR1 rats have been used to decipher the mechanisms that lead to virus-induced T1D. Both animals develop -cell inflammation and hyperglycemia upon infection with Kilham Rat Virus (KRV). Our earlier in vitro and in vivo studies indicated that KRV-induced innate immune upregulation early in the disease course plays a causal role in triggering -cell inflammation and destruction. Furthermore, we recently found for the first time that infection with KRV induces inflammation in visceral adipose tissue (VAT) detectable as early as day 1 post-infection prior to insulitis and hyperglycemia. The proinflammatory response in VAT is associated with macrophage recruitment, proinflammatory cytokine and chemokine upregulation, endoplasmic reticulum (ER) and oxidative stress responses, apoptosis, and downregulation of adipokines and molecules that mediate insulin signaling. Downregulation of inflammation suppresses VAT inflammation and T1D development. These observations are strikingly reminiscent of data from obesity and type 2 diabetes (T2D) in which VAT inflammation is believed to play a causal role in disease mechanisms. We propose that VAT inflammation and dysfunction may be linked with the mechanism of T1D progression.